2016
DOI: 10.1111/cch.12404
|View full text |Cite
|
Sign up to set email alerts
|

Physical fitness in preschool children: association with sex, age and weight status

Abstract: Sex differences in physical fitness are evident at an early age; in addition, the relationship between physical fitness and BMI is inconsistent in preschool children. The improvements of physical fitness performance and its association with physical activity could be important for the health of children, particularly in obesity prevention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
28
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 26 publications
7
28
0
7
Order By: Relevance
“…Moreover, Reilly et al () showed that a PA programme in a nursery (three 30‐min sessions a week over 24 weeks) did not reduce BMI in preschoolers. Along the same lines, Latorre Román et al () argued that the relationship between physical fitness and BMI is inconsistent in preschool children. Conversely, overweight children (ages 43 to 84 months) show lower performance in gross motor skills in relation to healthy‐weight children (Krombholz, ).…”
Section: Discussionmentioning
confidence: 96%
“…Moreover, Reilly et al () showed that a PA programme in a nursery (three 30‐min sessions a week over 24 weeks) did not reduce BMI in preschoolers. Along the same lines, Latorre Román et al () argued that the relationship between physical fitness and BMI is inconsistent in preschool children. Conversely, overweight children (ages 43 to 84 months) show lower performance in gross motor skills in relation to healthy‐weight children (Krombholz, ).…”
Section: Discussionmentioning
confidence: 96%
“…35 These findings are consistent with other reports considering PF and GMC in a univariate fashion. 37,38 The novel finding was that this increase was greater in GMC z than in PF z , which may reflect a non-synchronicity in their developmental timing and tempo across age.…”
Section: Discussionmentioning
confidence: 93%
“…Moreover, the other authors [9] indicated also that BMI-group-related differences in physical fitness can already be present in preschool-age children. Accordingly, Vameghi et al [20] suggested that both overweight and obese children have lower performance in fitness tests than normal-weight children [20] Otherwise, in the study with Spain pre-schoolers, BMI did not correlate with physical fitness [8]. It has been consistently reported that a low level of cardiorespiratory fitness and muscular strength in children are associated with low bone mass, metabolic risk factors, cardiovascular diseases and premature mortality later in life [17].…”
Section: Discussionmentioning
confidence: 94%
“…However, the reported level of physical activity (PA) and physical fitness of children has decreased during the last decades [5]. In addition, physical fitness, adiposity and the distribution of body fat during childhood have shown a high correlation with cardiovascular health in adulthood [8].…”
Section: Introductionmentioning
confidence: 99%